2012
DOI: 10.1210/en.2011-1543
|View full text |Cite
|
Sign up to set email alerts
|

Conditional Deletion of β-Catenin in Mammary Epithelial Cells of Ron Receptor, Mst1r, Overexpressing Mice Alters Mammary Tumorigenesis

Abstract: The Ron receptor tyrosine kinase (macrophage stimulating 1 receptor) is overexpressed in approximately 50% of human breast cancers. Transgenic mice overexpressing Ron in the mammary epithelium [mouse mammary tumor virus driven (MMTV)-Ron expressing mice] develop mammary tumors that exhibit up-regulation of ␤-catenin and ␤-catenin target genes. ␤-Catenin has been shown to be a mediator of mammary tumorigenesis in various breast cancer models, including downstream of Ron. However, the in vivo impact of a conditi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 30 publications
0
17
0
Order By: Relevance
“…This is an HGFL dependent event whereby activation of Ron by ligand stimulation leads to β-catenin nuclear localization and subsequent increases in c-myc and cyclin D1 [42]. Further, we demonstrated the important requirement for β-catenin in mammary tumorigenesis, as loss of β-catenin leads to a delay in mammary hyperplasia and reduced the metastatic burden in mice that overexpress Ron in the mammary epithelium [43]. Additionally, work in the prostate has supported the role of Ron in β-catenin activation where overexpression of Ron leads to accumulation of β-catenin protein and increased pErk [44].…”
Section: Ron and Cancermentioning
confidence: 95%
“…This is an HGFL dependent event whereby activation of Ron by ligand stimulation leads to β-catenin nuclear localization and subsequent increases in c-myc and cyclin D1 [42]. Further, we demonstrated the important requirement for β-catenin in mammary tumorigenesis, as loss of β-catenin leads to a delay in mammary hyperplasia and reduced the metastatic burden in mice that overexpress Ron in the mammary epithelium [43]. Additionally, work in the prostate has supported the role of Ron in β-catenin activation where overexpression of Ron leads to accumulation of β-catenin protein and increased pErk [44].…”
Section: Ron and Cancermentioning
confidence: 95%
“…Activation of β-catenin can occur directly through Ron-induced phosphorylation of residues Tyr 654 and Try 670 resulting in β-catenin nuclear translocation and enhanced transcription of cyclin D1 and c-Myc target genes [ 14 ]. Moreover, genetic ablation of β-catenin reduced Ron-directed mammary tumor growth and metastasis, as well as cell proliferation in vitro [ 14 ], which was further confirmed in a study utilizing a transgenic mouse model with Ron overexpression in the mammary epithelium and targeted deletion of β-catenin [ 21 ]. Thus, understanding how perturbations in the Ron-β-catenin signaling axis affect the therapeutic response of breast cancers with a highly metastatic phenotype is critical for lessening the deaths associated with metastatic disease.…”
Section: Introductionmentioning
confidence: 91%
“…Expression analysis of molecules involved in cell cycle progression revealed that RON overexpression led to increased phosphorylation of MAPK and b-catenin, and up-regulation of bcatenin target genes such as cyclin D1 and c-Myc (Zinser et al 2006). Conditional deletion of b-catenin in the context of RON overexpression resulted in delayed onset of mammary hyperplastic nodules and tumorigenesis, decreased tumor growth, and decreased liver metastasis at the studied time point, revealing a contributing, but not essential, role of b-catenin in mammary tumorigenesis downstream from RON (Wagh et al 2012). Gene expression analysis of the A2780 ovarian cell line has shown upregulation of several MAPK target genes in response to MSP (Chaudhuri et al 2011).…”
Section: Signaling Pathways Downstream From Ron In Cancer Progressionmentioning
confidence: 79%